Mixed Strains of Bacillus velezensis PBS-17, Lactiplantibacillus plantarum J-135, and Saccharomyces cerevisiae DAE-4 Increase the Storage Capacity of Fermented Feed and Silage - Eun-Jae Park; Moon Joo Kim; Bori Lee; Hyun-Jae Jang; Seung Woong Lee (Fermentation)
In this study, we investigated whether three microbial strains, Lactiplantibacillus plantarum J-135, Saccharomyces cerevisiae DAE-4, and Bacillus velezensis PBS-17, could be used to reduce mold growth and spoilage during the production of fermented feed. These microorganisms were isolated and characterized via an evaluation of their antibacterial activity, enzymatic activity, bile acid resistance, and acid tolerance. L. plantarum J-135 and S. cerevisiae DAE-4 demonstrated excellent acid tolerance and bile acid resistance, and L. plantarum J-135 exhibited antibacterial activity against Salmonella species. B. velezensis PBS-17 showed the greatest protease, cellulase, α-amylase, and phytase enzymatic activities, and displayed antibacterial activity against Fusarium solani, Aspergillus flavus, Penicillium sp., and Fusarium oxysporum. The three isolated strains were diluted to the same concentration (1:1:1) to create a culture solution, which was added to a standard feed (experimental group) to prepare fermented feed. This was compared with feed treated with a commercially available single probiotic preparation (control group 1) or a mixed microbial preparation that was composed of multiple strains, including B. subtilis. The feed treated with the single probiotic preparation spoiled after 21 days due to insufficient lactic acid bacteria growth, whereas the feed treated with the mixed microbial preparation exhibited mold growth after 14 days. The bacteria and fungi that cause spoilage during fermented feed production were effectively controlled in feed treated with L. plantarum J-135, S. cerevisiae DAE-4, and B. velezensis PBS-17. Therefore, the mixture of these three microbial strains may reduce the risk of spoilage during fermented silage and feed processing, thereby improving storage properties and stability.